Optimization of hydraulic fracturing wastewater management alternatives: A hybrid multi-objective linear programming model - Shamloo, Nazila; Bakhtavar, Ezzeddin; Hewage, Kasun; Sadiq, Rehan (Journal of cleaner production, 2021)
Production of high volumes of wastewater by hydraulic fracturing operations is a challenging issue in the unconventional gas industry in North America. A scheduling-based solution is required to optimally manage the produced wastewater. This study develops a novel, hybrid, multi-objective linear programming model to optimize hydraulic fracturing wastewater management alternatives. Minimizing overall wastewater treatment cost, environmental impacts, and undesirable deviations from different goals were simultaneously considered the main objectives of the system. The model used data from a case example operating for 31 weeks, and it determined the volume of wastewater and treated water over all periods. The results indicated that onsite treatment is the best possible alternative for reuse in subsequent fracking, in those weeks in which all constraints were satisfied. Offsite treatment was the second ranking alternative when the volume of wastewater was higher than the capacity of onsite treatment, and deep well injection was the result when no water was needed for subsequent fracking. A sensitivity analysis was conducted by weighting the objectives to express their importance levels. Compared to other objectives, environmental impact had greater effect on the selection of the optimal alternatives over each period. [Display omitted] •A multi-objective framework was developed based on goal and linear programming.•Objectives were weighted based on different weighting scenarios.•The model can optimally solve hydraulic fracturing wastewater management problems.•The model can be simply updated and applied in water and wastewater management.